The Effect of Palpebral Fissure Height in Primary Gaze Position on Tear Film Stability - Ana Čović; Igor Petriček; Martina Tomić (Acta Clinica Croatica, 2023)
This study aimed to investigate the effect of palpebral fissure height in primary gaze position in healthy individuals on tear film stability. In this cross-sectional study, 120 subjects (60 male and female each) were enrolled and divided according to age into two groups, i.e., group 1 (aged 18-50 years) and group 2 (aged 51 and older). Palpebral fissure height on both eyes was measured in primary gaze position with a clear plastic ruler held in a central vertical position between the upper and lower lid margin, and the standard tear break-up time (TBUT) test was performed to evaluate tear film stability. Palpebral fissure height was significantly higher in younger than older subjects in all measurements on both eyes (p<0.001), and TBUT was shorter in older than in younger subjects. In all subjects included in the study, palpebral fissure height was not related to TBUT (p=0.589). However, analyzing the two age groups separately, a significant negative correlation was found between the palpebral fissure height and TBUT in both groups of younger (p<0.001) and older (p=0.009) subjects. In conclusion, an enlarged exposed ocular surface due to higher palpebral fissure height in healthy individual’s primary gaze position negatively affects tear film stability expressed by TBUT.